EFFICIENT TRAFFIC CLEARANCE FOR EMERGENCY VEHICLE - st Abhimanyu C V,; Mannickathan, Prof. Gripsy Paul (International Journal of Psychosocial Rehabilitation, 2020)
In this fast moving world everyone lives a rush life. The circumstances in roads are also not different from this. The number of accidents are also increasing accordingly. It is inevitable for an emergency vehicle to reach on right time, where accident occurred to reduce its intensity. In order to tackle the problems related to emergency vehicle being get stuck in a traffic congestion this paper presents an efficient way of traffic clearance for emergency vehicle.